(3х+1)(4х-2)-6(2х-1)^2+14 упростите выражение

 (3х+1)(4х-2)-6(2х-1)^2+14 упростите выражение
Гость
Ответ(ы) на вопрос:
Гость
[latex](3x+1)(4x-2)-6(2x-1)^2+14= \\ \\ =12x^2-6x+4x-2-6(4x^2-4x+1)+14= \\ \\ = 12x^2-6x+4x-2-24x^2+24x-6+14= \\ \\ =-12x^2+22x+6[/latex]
Гость
(3x+1)(4x-2)-6(2x-1)^2+14=12x^2-2x-2-6*(2x-1)^2+14=12x^2-2x-2-6*(4x^2-4x+1)+14=12x^2-2x-2-(24x^2-24x+6)+14=12x^2-2x-2-24x^2+24x-6+14=-12x^2-2x-2+24x-6+14=-12x^2+22x-2-6+14=-12x^2+22x-8+14=-12x^2+22x+6
Не нашли ответ?
Ответить на вопрос
Похожие вопросы